Using the energy accountancy equation to modify punch design in presses - RICHARDS, E. J. (Archives of Acoustics, 1985)
Estimations of overall noise efficiency are difficult to give since the measurement of the mechanical energy used by the press is not easy to define, let alone measure. Flywheel machines take the power from the flywheel, which slows down, but much of this is absorbed in accelerating the mechanism and in other ways. However, we can estimate that, of the flywheel energy which is available, me 0.0001 goes into noise. This is a small fraction and far to low to considering for any other purpose. Thus, once again, the argument that noise is wasted energy cannot be a valid reason for noise reduction. The reason for reducing noise must hinge on the need to meet deafness limits, and must be related to e 85 or 90 dB (A) limit on L_Aeq,8L. This is an average radiated acoustical energy aching the ear of an operator and must be related to the average energy radiated from the whole machine during the same period of time. Knowledge of e frequency of the noise concerns us only in the sense that an A-weighting with frequency must be added to reflect the difference in the subjective acceptability of noise of different frequencies. * Presently at Department of Ocean Engineering, Florida Atlantic University, Boca aton, Florida, USA.